1964
DOI: 10.21236/ad0600601
|View full text |Cite
|
Sign up to set email alerts
|

The Accuracy of the Azon Guided Bomb as Affected by Battle Conditions in World War Ii

Abstract: The AZON bomb was studied as part of an investigation into the effects of battle stress on the accur cy of control systems in which a human operator is required to perform a task of tracking and guiding a missile to a target. The AZON rystem provided an example of a single axis (AZimuth ONly) control with acceleration response of low stiffness and long time delay. These features could be easily simulated for the purpose of establishing a basis for comparison with results of experimental studies of human operat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…This is different from the measurement of deviation from track under first-person view (FPV) condition, which is more similar to the pursuit tracking task [11,14]. The unaided radio-guided azimuth-only "AZON" bombs results reported by Anthony et al [12] showed a mean aiming error of 1.7 mil (micro-radiant) and a mean oscillatory error of 1.65 mil over a distance of 15,000 ft (with a total travel time of sim20 s), while tests with wire-guided TOW missile reported by Penetar et al [13] showed a mean tracking error of 0.446 mil with horizontal and vertical standard deviation of 0.138 mil and 0.112 mil, respectively, over a distance of 2,000 m ( with a total travel time of ∼ 10 s).…”
Section: Literature Reviewmentioning
confidence: 80%
See 2 more Smart Citations
“…This is different from the measurement of deviation from track under first-person view (FPV) condition, which is more similar to the pursuit tracking task [11,14]. The unaided radio-guided azimuth-only "AZON" bombs results reported by Anthony et al [12] showed a mean aiming error of 1.7 mil (micro-radiant) and a mean oscillatory error of 1.65 mil over a distance of 15,000 ft (with a total travel time of sim20 s), while tests with wire-guided TOW missile reported by Penetar et al [13] showed a mean tracking error of 0.446 mil with horizontal and vertical standard deviation of 0.138 mil and 0.112 mil, respectively, over a distance of 2,000 m ( with a total travel time of ∼ 10 s).…”
Section: Literature Reviewmentioning
confidence: 80%
“…The problem of measuring UAS deviation from intended track towards a virtual target in 3D space under visualline-of-sight condition is analogous to the deviation measurement for the human compensatory tracking task [11], though with the added delay in visual-feedback due to the command transmission time and flight control response time more similar to that of human bombs [12,13]. This is different from the measurement of deviation from track under first-person view (FPV) condition, which is more similar to the pursuit tracking task [11,14].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the control of UAS also involves a time-lag associated with visual identification of UAS attitude and heading as well as the delay between operator command and UAS response due to the multi-rotor flight dynamics. As such, the task of controlling the UAS towards a target point is analogous to the compensatory tracking task of remote controlling and guiding a bomb towards a target [49], [50], though the vehicle dynamic is different. Experiments conducted with unaided radio-guided "AZON" bomb [49], which could only be controlled by changing the azimuth angle, showed that for a target 15,000 ft below the bomber aircraft (giving the bomb a travel time of ∼ 20 s), a mean error (n = 67) of 1.7 micro-radiant (mil) from the intended target with a mean oscillatory error of 1.65 mil was observed.…”
Section: Visual Line Of Sight (Vlos) Type Operationsmentioning
confidence: 99%
“…As such, the task of controlling the UAS towards a target point is analogous to the compensatory tracking task of remote controlling and guiding a bomb towards a target [49], [50], though the vehicle dynamic is different. Experiments conducted with unaided radio-guided "AZON" bomb [49], which could only be controlled by changing the azimuth angle, showed that for a target 15,000 ft below the bomber aircraft (giving the bomb a travel time of ∼ 20 s), a mean error (n = 67) of 1.7 micro-radiant (mil) from the intended target with a mean oscillatory error of 1.65 mil was observed. A more recent study with wire-guided TOW missile [51], which could be controlled in both the azimuth and elevation directions, for a target that is 2,800 -3,000 m away (for a controlled duration of ∼ 15 s) the horizontal mean tracking errors (n = 86) is 0.612 mil with a standard deviation of 0.2566 mil and the vertical mean tracking error is 0.008 mil with a standard deviation of 0.0698 mil.…”
Section: Visual Line Of Sight (Vlos) Type Operationsmentioning
confidence: 99%